Microbial and heavy metals contaminations among the commonly sold vegetables in Lagos State, Nigeria (2021)
Assessments of heavy metals and microbial contaminations of vegetables cannot be overemphasized as vegetables are important components of human diet. Intake of heavy metalcontaminated vegetables poses high risk to human health. Heavy metal concentrations and microbial contamination in twelve (12) most consumed vegetables Talinum triangulare, Telfairia occidentalis, Vernomia amygdalina, Amaranthus hybridus, Ocimum gratissimum, Celosia argentea, Taraxacum officinale, Piper guineense, Lactuna sativa, Gnetum africanum, Gongronema latifolium, and Pterocarpus mildraedii was carried out using standard laboratory procedures. Antibiotic susceptibility testing against 6 structurally unrelated antibiotics (clindamycin, cefoxitin, cloxacillin, gentamycin, erythromycin and ciprofloxacin) were done on the isolates obtained using disk diffusion method. Total of 36 bacteria isolates were obtained comprising of Staphylococcus aureus (12, 33.3%), Bacillus spp. (23, 63.9%), Micrococcus spp. (1, 2.80%) which were identified based on cultural and biochemical identification. Twenty three Fungal isolates involving Aspergillus acelatus (7, 30.43%), A. fumigatus (7, 30.43%), A. niger (5, 21.74%) and Penicillium Spp (4, 17.40%) were identified based on cultural and fungal staining technique. The overall number of susceptibility for ciprofloxacin (72%), erythromycin (61%) and gentamicin (50%) were recorded. Antibiotic resistance were recorded for clindamycin (66%), cloxacillin (61%) and cefoxitin (45%). The heavy metals concentration on the examined vegetables were above WHO acceptable limit of 0.3mg/kg, 0.2mg/kg and 1.30mg/kg for Pb, Cd and Cr respectively. The bacteria isolated harbored antibiotic resistance mechanisms against antibiotics which calls for urgent measures to minimize all possible routes for contaminations.